2003
DOI: 10.1152/physiolgenomics.00058.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of temporal patterns of gene expression in the uteri of immature, ovariectomized mice following exposure to ethynylestradiol

Abstract: Estrogen induction of uterine wet weight provides an excellent model to investigate relationships between changes in global gene expression and well-characterized physiological responses. In this study, time course microarray GeneChip data were analyzed using a novel approach to identify temporal changes in uterine gene expression following treatment of immature ovariectomized C57BL/6 mice with 0.1 mg/kg 17alpha-ethynylestradiol. Functional gene annotation information from public databases facilitated the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 85 publications
3
38
0
Order By: Relevance
“…A conservative statistical P1(t) cutoff of 0.9999 combined with a differential expression of Ϯ1.5 fold relative to TMVCs was used to identify lists of differentially active genes. Gene expression responses to EE alone displayed the expected complex transcriptional profile as reported previously (Fertuck et al, 2003;Kwekel et al, 2005) with a total of 3,746 features, representing 2,753 unique genes, identified as differentially 3. EE, TCDD, and EE ϩ TCDD effects on temporal uterine weights.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…A conservative statistical P1(t) cutoff of 0.9999 combined with a differential expression of Ϯ1.5 fold relative to TMVCs was used to identify lists of differentially active genes. Gene expression responses to EE alone displayed the expected complex transcriptional profile as reported previously (Fertuck et al, 2003;Kwekel et al, 2005) with a total of 3,746 features, representing 2,753 unique genes, identified as differentially 3. EE, TCDD, and EE ϩ TCDD effects on temporal uterine weights.…”
Section: Resultsmentioning
confidence: 59%
“…Functional annotation of gene expression responses was performed using data extracted from public databases and published literature. The functions of EE differentially expressed genes have been associated with transcription factors, mRNA and protein synthesis, cell cycle regulation, cellular proliferation, energetics and structural constituents (Fertuck et al, 2003;Moggs et al, 2004;Kwekel et al, 2005). Functional annotation of EE-mediated gene expression responses that were inhibited upon cotreatment with TCDD were associated with the regulation of cell proliferation and growth, water/ion E4 M4 E12 M12 T12 E24 M24 E72 M72 T24 T72 T4 EE EE+TCDD TCDD E4 E12 E24 E72 M4 M12 M24 M72 T4 T12 T24 T72 A B…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is another compelling alternate explanation. Using gene screen technology, Fertuck et al [22] have recently shown that 17β-estradiol induces arginase I (AGI), an enzyme that utilizes arginine to produce ornithine, the first step in polyamine production. Since polyamines are well known to have critical roles in cell physiology, including enhancement of transcription factor binding and coactivator function, modulation of polyamines is a likely outcome of estrogen's action on cells.…”
Section: Discussionmentioning
confidence: 99%
“…To independently examine the estrogen-like gene expression responses of TCDD, six genes were chosen for verification by QRTPCR. Arginine-rich, mutated in early stage tumors (Armet), asparagine synthetase (Asns), activating transcription factor 4 (Atf4), expressed in nonmetastatic cells 1 (Nme1), proliferating cell nuclear antigen (Pcna), and solute carrier family 25 member 5 (Slc25a5) were specifically selected because they displayed similar responses to EE and TCDD and have been previously identified as estrogen inducible in the rodent uterus in independent studies (Watanabe Fertuck et al, 2003;Moggs et al, 2004b;Kwekel et al, 2005). QRTPCR analyses confirmed the microarray results indicating these genes were induced by both EE and TCDD (Fig.…”
Section: Comparison Of Uterine Gene Expression Responses To Tcdd and Eementioning
confidence: 99%